Institutional design and voting power in the European Union - Cichocki, Marek A.; Życzkowski, Karol 1960- (Routledge, 2016)
Leading global experts in the field of politics and mathematics bring forth key insights on how voting power should be allocated between EU member states, and what the policy consequences are of any given institutional design. Close attention is paid to the practical implications of decision-making rules, the nature and distribution of power, and the most equitable ways to represent the preoccupations of European citizens both in the Council and European Parliament. Highly theoretical and methodologically advanced, this volume is set to enrich the debate on the future of the EU's institutional design. A valuable source of information to scholars of political science, European studies and law, as well as to people working on game theory, theory of voting and, in general, applications of mathematics to social science.